2001
DOI: 10.1159/000049281
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Academic Self-Image in Adolescence

Abstract: The aim of this paper was to specifically analyse the relationship between the different components of academic self-image, defined as the way adolescents represent themselves as students, and self-reported depressive symptoms, assessed with the Children’s Depression Inventory (CDI), in a non-clinical sample of 298 adolescents. We considered both adolescents’ beliefs about their own cognitive functioning in academic performance and beliefs about their emotional attitude in achievement situations. Our data indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…In line with the majority of previous studies (Economou & Angelopoulos, 1989;Kaltiala-Heino et al, 1998;Kovacs & Goldston, 1991;Masi et al, 2000;Puig-Antich et al, 1993;Reinherz et al, 1991;Slotkin et al, 1988)-if not all (Lewinsohn et al, 1995;Masi et al, 2001;Reinherz et al, 1991)-we found that self-reported depression was associated with poor academic achievement in terms of low school marks. The lower the GPA, the more common was depression.…”
Section: Discussionsupporting
confidence: 92%
“…In line with the majority of previous studies (Economou & Angelopoulos, 1989;Kaltiala-Heino et al, 1998;Kovacs & Goldston, 1991;Masi et al, 2000;Puig-Antich et al, 1993;Reinherz et al, 1991;Slotkin et al, 1988)-if not all (Lewinsohn et al, 1995;Masi et al, 2001;Reinherz et al, 1991)-we found that self-reported depression was associated with poor academic achievement in terms of low school marks. The lower the GPA, the more common was depression.…”
Section: Discussionsupporting
confidence: 92%
“…Mental health problems make adolescents face with a decline in academic achievement [67], which in turn results in school absence, poor grades, and even repeating a grade in school [68]. Those adolescents reporting high level of mental health problems are more likely to perceive themselves as less academically competent [69], and they display low academic achievement in school [70]. When schools identify problem behaviors with programs of intervention, it is likely to improve academic achievement of adolescents [71].…”
Section: Discussionmentioning
confidence: 99%
“…These stresses in relations to school may, in turn, have a negative impact on students’ psychological adjustment (Sund et al , 2003). Evidence also exists to suggest that scholastic failure is associated with psychological disorders, such as depression (see Masi, Tomaiuolo, Sbrana et al , 2001; Masi, Brovedani, Poli, 1998). Additionally, stressful events during adolescence may set in motion a self‐perpetuating cycle where stress and psychological symptoms contribute to each other (Compas, 1987b).…”
Section: Introductionmentioning
confidence: 99%